2003
DOI: 10.1034/j.1600-0528.2003.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries and micronutrient intake among urban South African children: a cohort study

Abstract: The association of micronutrient intake with caries was weak, isolated and not clinically relevant. Micronutrient intake was not an indicator of the presence or absence of caries among the children studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
14
2
3
Order By: Relevance
“…Findings from previous studies are contradictory, with reports of no relationship [10], a weak relationship [9] and even a direct relationship between micronutrient deficiencies and dental caries [7,11,13]. However, studies that have related malnutrition or micronutrient deficiencies to dental caries in the primary dentition offer indirect evidence of this association [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from previous studies are contradictory, with reports of no relationship [10], a weak relationship [9] and even a direct relationship between micronutrient deficiencies and dental caries [7,11,13]. However, studies that have related malnutrition or micronutrient deficiencies to dental caries in the primary dentition offer indirect evidence of this association [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The clarification of this issue is important because it is the basis for the planning of prevention strategies aimed at adverse health conditions in childhood. In one of the few longitudinal studies with a reasonable sample size, the authors investigated 21 micronutrients in 259 South African children at 12 months of age and reported an effect on oral health at five years of age [9]. However, the authors found a weak, isolated association without clinical importance between magnesium intake and dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A amostragem por conveniência realizada neste estudo pode gerar potenciais vieses de seleção, pois não há como saber se todas as pessoas Tabela 2 Índices CPOD e ceod, desvio-padrão (DP) e livres de cárie, por faixa etária, na população rural ribeirinha, rio Machado e rio Além disso, aos 12 anos de idade, 33% da população estudada possui CPOD > 3,0; e 30% são livres de cárie, sugerindo uma concentração da doença cárie, fato observado em diversos estudos, nas mais diferentes populações 3,7,16,17,18 . Nesse sentido, Narvai et al 3 afirmam que, no Brasil, 20% dos escolares passaram a concentrar 60% da carga da doença.…”
Section: Discussionunclassified
“…According to MacKeown et al [2003], vitamin B 12 was significantly associated with caries incidence. In addition, Kwan et al [1998] reported a higher caries incidence in children with low levels of folic acid.…”
mentioning
confidence: 99%